CRITICAL ANALYSIS OF MINI UNMANNED AERIAL VEHICLES (UAV) DEVELOPMENT CAPABILITIES AND PERSPECTIVES OF EFFECTIVE INTEGRATION IN HORTICULTURAL AGROECOSYSTEMS IN ROMANIA - Iagăru, Pompilica; Boșcoianu, Mircea; Cioca, Ionel-Lucian; Petre, Ioana Mădălina; Pop, Sebastian; Sârbu, Flavius Aurelian; Iagăru, Romulus (Scientific Papers Series Management, Economic Engineering in Agriculture and Rural Development, 2023)
The present attests to the development of autonomous unmanned aircraft systems and their widespread use in various fields. The article presents the level of development of mini UAVs, the rapid growth of their use in various fields and challenges for various civil applications. At the same time, current research trends are highlighted and future perspectives for use in precision horticulture are identified. For this, the research methodology used included both quantitative and qualitative methods of the type of secondary analysis of statistical data and specialized literature, respectively the SWOT analysis model, supplemented with the observation method. The realization of the study allowed to obtain an overview of the level of development of mini UAV and the possibilities of increasing the degree of use in various fields.
Keywords: research; horticulture; precision; mini Unmanned Aerial Vehicles (UAV); perspectives